2019
DOI: 10.1002/ece3.5024
|View full text |Cite
|
Sign up to set email alerts
|

Availability of food resources and habitat structure shape the individual‐resource network of a Neotropical marsupial

Abstract: Spatial and temporal variation in networks has been reported in different studies. However, the many effects of habitat structure and food resource availability variation on network structures have remained poorly investigated, especially in individual‐based networks. This approach can shed light on individual specialization of resource use and how habitat variations shape trophic interactions. To test hypotheses related to habitat variability on trophic interactions, we investigated seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 72 publications
(115 reference statements)
3
24
0
3
Order By: Relevance
“…The frugivorous R. macrurus exhibited a dynamic trophic niche across seasons. In the Cerrado, the warm-wet season usually supports a higher abundance and diversity of fruit and arthropod resources (Gouveia & Felfili, 1998;Pinheiro et al, 2002;Silva et al, 2011), a pattern previously documented in our study area (see Camargo, Oliveira, et al, 2019, Our results indicated that the arboreal forest-specialist R. macrurus feeds mostly on fruit, with little contribution of insects to its diet. It was understood that this species is a frugivore and granivore (Paglia et al, 2012), but this is now verified based on fecal content measured in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The frugivorous R. macrurus exhibited a dynamic trophic niche across seasons. In the Cerrado, the warm-wet season usually supports a higher abundance and diversity of fruit and arthropod resources (Gouveia & Felfili, 1998;Pinheiro et al, 2002;Silva et al, 2011), a pattern previously documented in our study area (see Camargo, Oliveira, et al, 2019, Our results indicated that the arboreal forest-specialist R. macrurus feeds mostly on fruit, with little contribution of insects to its diet. It was understood that this species is a frugivore and granivore (Paglia et al, 2012), but this is now verified based on fecal content measured in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Understanding individual specialization can be particularly useful to elucidate population niche patterns for animal species that experience intense inter-and intraspecific competition and marked seasonality regarding food-resource availability (Bolnick et al, 2010;Camargo, Oliveira, et al, 2019;Svanbäck & Bolnick, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is hard to predict how behaviorally flexible individuals with different wing shapes can be during transitions between seasons. Changes in habitat structure and food availability in a Neotropical seasonal dry forest has been linked with differential spatial and resource use between individuals in a mammal species [81]. Thus, it is possible that both variables play a role on how bats with different wing morphologies explore and specialize in their environment.…”
Section: Plos Onementioning
confidence: 99%
“…Network approaches can provide useful insights into inter-individual variation in resource use [23][24]. The existing studies that have examined networks composed of individuals within a population have reported different levels of specialization [25][26], in which the diets of specialist individuals are nested within the diets of the generalists [7,27].…”
Section: Introductionmentioning
confidence: 99%